Endogenous expression mapping of malignant melanoma by mass spectrometry imaging. Issue 1 (6th August 2018) - Sugihara, Yutaka; Rivas, Daniel; Malm, Johan; Szasz, Marcell; Kwon, HoJeong; Baldetorp, Bo; Olsson, Håkan; Ingvar, Christian; Rezeli, Melinda; Fehniger, Thomas E.; Marko‐Varga, György
Abstract: Background: Currently, only a limited number of molecular biomarkers for malignant melanoma exist. This is the case for both diagnosing the disease, staging, and efficiently measuring the response to therapy by tracing the progression of disease development and drug impact. There is a great need to identify novel landmarks of disease progression and alterations. Methods: Matrix‐assisted laser desorption ionisation mass spectrometry imaging (MALDI‐MSI) has been developed within our group to study drug localisation within micro‐environmental tissue compartments. Here, we expand further on this technology development and introduce for the first time melanoma tumour tissues to map metabolite localisation utilising high resolution mass spectrometry. MALDI‐MSI can measure and localise the distribution pattern of a number of small molecule metabolites within tissue compartments of tumours isolated from melanoma patients. Data on direct measurements of metabolite identities attained at the local sites in tissue compartments has not been readily available as a measure of a clinical index for most cancer diseases. The current development on the mapping of endogenous molecular expression melanoma tumours by mass spectrometry imaging focuses on the establishment of a cancer tissue preparation process whereby a matrix crystal formation is homogenously built on the tissue surface, providing uniform molecular mapping. We apply this micro‐preparation technology to disease presentation by mapping the molecular signatures from patient tumour sections. Results: We have automated the process with a micro‐technological dispensing platform. This provides the basis for thin film generation of the cancer patient tissues prior to imaging screening. Compartmentalisation of the tumour regions are displayed within the image analysis interfaced with histopathological grading and characterisation. Conclusions: This enables site localisation within the tumour with image mapping to disease target areas such as melanoma cells, macrophages, and lymphocytes.